Racism in Medicine: Patient Care and Service: Invited Editorial - Hotine, Emily (Journal of the Nuffield Department of Surgical Sciences, 2020)
Both the Black Lives Matter movement and the COVID-19 pandemic have brought questions of racism to the forefront of discourse. Backlash in response to the Black Lives Matter movement through the popularisation of the phrases “all lives matter” and “blue lives matter” has further demonstrated the fact that racism is still prevalent in modern society. The higher mortality rate of black patients with COVID-19 compared to white patients1 has highlighted the structural inequalities in healthcare and the urgent need for further research into these inequalities. Racism is apparent in every level of the healthcare system, from education, to employment, to patient care, but the history and evolution of racism in healthcare is long and complex. Racial inequality in healthcare is inextricably linked with socio-economic and cultural factors. Although further research is required to fully understand these intersections, the data that is currently available does begin to shed some light on the ways in which this racism manifests.